Steroid-Induced Ocular Hypertension in a Pediatric Patient with Acute Lymphoblastic Leukemia: A Case Report - Hung-Yin Lai; Ing-Chou Lai; Po-Chiung Fang; Chih-Cheng Hsiao; Yu-Ting Hsiao (MDPI AG, 2022)
Glucocorticoids play a pivotal role in therapeutic protocols in acute lymphoblastic leukemia (ALL) treatment. Systemic steroids are known to be less likely to elevate the intraocular pressure when compared to topical administration, and reports addressing hypertensive ocular response in the Asian pediatric ALL population are currently limited. We report a case of a nine-year-old girl with acute lymphoblastic leukemia (ALL) who was found to have highly elevated intraocular pressure (IOP) during maintenance treatment when taking oral dexamethasone (6 mg/m2/day). Her IOP increased on day 5 after taking dexamethasone, reached a peak on day 7 or 8, and returned back to baseline on day 13 before anti-glaucoma medications were used. Thus, we prescribed IOP-lowering agents for 10 consecutive days starting on the day oral dexamethasone was administered, and observed that not only did the peak levels lower remarkably, but the IOP levels returned to baseline more rapidly as well.